Faktor-Faktor Internal Yang Berperan Dalam Keberhasilan Terapi Pasien Terhadap Penyakit Morbus Hansen Di Kota Bandar Lampung - Siti Zahnia; Tri Umiana Soleha; Ety Apriliana (MAJORITY, 2020)
Morbus Hansen (MH) is a chronicinfectiousdisease caused by Mycobacterium leprae. Morbus Hansen's disease is a national public health problem in Indonesia. The cure rate in Lampung in 2014 is about 83.3% for PB and 60.1% for MB. The cure rate has not yet reached the target release from treatment, which is >90%. Low achievement of MH cure rate can be caused by patients who’re not regularly taking the medication. The lack of MH cure rate can be caused byseveralfactors, which are externalamd internal factors. This study aimed to determine the internal factors that associated with therapy success of Morbus Hansen's disease in Bandar Lampung. This study is an observational study with cross sectional design.The sample in this study isMH patients who take medication to Puskesmas in Bandar Lampung region, about 42 patients. Data then analyzed using chi-square test. The results showed that out of 42 respondents, the success of MH therapy is bigger on the child's age, female gender, higher education, not working, medication adherence, good knowledge and good socio-economic. From the bivariate analysis, it’s known that there is influence of age (p=0,017), knowledge (p=0,030) and socio-economic on the successful of therapy (p=0.002), while gender, education and employment do not affect the success of the therapy (p = 0.190; p = 0.064; p = 0.355). From six internal factors analyzed in this studythere are only age, level of knowledge and socio-economic thatassociated to the successful therapyof patients withMorbus Hansen's disease.